DISKRESI POLISI DALAM PENANGANAN TINDAK PIDANA PENCURIAN: Studi Kasus di Wilayah Hukum Polsek Pidie - Izwany, Bonita; Diana, Ema (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to find out about police discretion in handling theft crimes (case study in the jurisdiction of the Pidie Police). The research method used in compiling this thesis is a qualitative method to obtain data in the field, the author uses the Library research method (library research) and field research (field research), namely by using observation, interview, and documentation techniques. The results of the study indicate that the Police's efforts in the form of preventing theft crimes by providing protection to the public so as not to become victims of other thefts and the Mechanism taken by the police in resolving the problem of theft against reports received by the police is the first by visiting the Crime Scene (TKP), examining the victim and witnesses or the Examination Report (BAP). 2. The obstacles faced by the police chief in resolving the existing problems are inadequate facilities and infrastructure, disconnected information networks, lack of evidence and witnesses, apathetic society, inadequate supporting facilities at the crime scene. The role of the police in handling cases of minor theft is based on the memorandum of understanding between the court, the prosecutor's office and the police which normatively states that if the stolen amount is less than two million five hundred thousand rupiah, it will be resolved in the village or from the police chief's program, namely restorative justice, if more than two million five hundred thousand rupiah is taken, it must be resolved in court, and if someone reports this minor theft crime, we will still process it by calling the suspects and victims or giving customary sanctions.